2008
DOI: 10.1002/mrd.20875
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of bovine cloned embryos at the four‐cell stage stimulated gene expression and in vitro embryo development

Abstract: Pre-implantation embryos produced by somatic cell nuclear transfer (SCNT) have varied developmental potentials. The majority of SCNT blastocysts do not develop to term, and the mechanisms inhibiting development are still largely unknown. Aggregation of cloned embryos has been attempted to compensate for the developmental deficiency of individual cloned embryos. In this report, we investigated the impact of aggregation of bovine cloned embryos at the four-cell stage on in vitro development and gene expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Blastocyst rates were also increased as a result of embryo aggregation as has previously been demonstrated for other species (Pedersen et al 2005, Zhou et al 2008, Ribeiro Ede et al 2009, Gambini et al 2012. A 24% increase in the capacity of morulae to develop into blastocysts was observed in the Dc2X group and 34% in the Ch2X group, when compared with their respective 1X groups.…”
Section: Effect Of Iscnt and Aggregation On In Vitro Development Of Dsupporting
confidence: 77%
See 1 more Smart Citation
“…Blastocyst rates were also increased as a result of embryo aggregation as has previously been demonstrated for other species (Pedersen et al 2005, Zhou et al 2008, Ribeiro Ede et al 2009, Gambini et al 2012. A 24% increase in the capacity of morulae to develop into blastocysts was observed in the Dc2X group and 34% in the Ch2X group, when compared with their respective 1X groups.…”
Section: Effect Of Iscnt and Aggregation On In Vitro Development Of Dsupporting
confidence: 77%
“…This approach, which is called embryo aggregation, results in higher blastocyst cell numbers, normalization of pluripotent gene expression and higher in vivo development in the mouse and miniature pigs (Boiani et al 2003, Balbach et al 2010, Siriboon et al 2014). Moreover, rates of blastocyst production improved for bovine and equine aggregated embryos as also did blastocyst cell numbers and pregnancy rates (Pedersen et al 2005, Zhou et al 2008, Ribeiro Ede et al 2009, Gambini et al 2012. Despite these promising reports, embryo aggregation has not been evaluated in felids or in iSCNT.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, interaction between Oct4 and Cdx2 determines TE differentiation [27]. It has been reported that embryo aggregation influences gene expression [4,7,9,28]. In mice, aggregation of SCNT embryos at the 4-cell stage results in Oct4 and Cdx2 expression similar to that of fertilized embryos [7,28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cloning efficiency is improved by aggregating two mouse SCNT embryos at the 4-cell stage [7]. Thus, the timing of aggregation is likely important for the production of high-quality SCNT embryos [9]. In bovine SCNT, however, there has been no report examining the effect of the timing of aggregation on cloning efficiency, and cloned calves have not been produced as a result of aggregation of SCNT embryos at the cleavage stage except for at the 1-cell stage [8,10].…”
mentioning
confidence: 99%
“…Embryo aggregation consists of placing more than one zona free embryos in the same well; some of the reported benefits in mammals are: improvement in embryo development in pig [6], equine [8,9], feline [10] and mouse [11], increasing the density of cells in the inner cell mass on cattle [12], blastocyst diameter in equine and in bovine [8,13], reduction in apoptosis in bovine and pigs [13,14,15], normalization of gene expression in bovine [15]and in some cases, it has also improved in vivo embryo development and early pregnancy rates in mouse [11], equine [8] and in cattle [13,16,17]. As a single clone may have epigenetic defects [15], embryo aggregation could compensate the reprogramming deficiencies through the interactions between blastomeres [11] or by paracrine pathways [11]. Indeed, it has been proposed that such interaction could also improve post implantation development [18].…”
Section: Introductionmentioning
confidence: 99%